Factor space and study the process of electricity consumption of iron ore enterprises - Сінчук, Олег Миколайович; Сінчук, Ігор Олегович; Ялова, Альона Миколаївна; Віннік, Марина Анатоліївна (Technology audit and production reserves, 2015)
In article results of researches of the analysis of energy consumption of the domestic mining enterprises with under-ground methods of mining iron ore are given. The structure of energy consumption is given. It was found that the main type of energy use is electricity. The relationship is shown between the consumption of electric power enterprises and the cost of mined iron ore. The need for process control of energy consumption and planning of energy consumption of enterprises is justified. The authors present a classification of factors that influence the effectiveness of the regulation system of electric energy specific losses. A method of creating factor system and integral indicator for controlling the energy supply companies have formulated. It is proposed a reasonable technique to implement effective process of power consumption control of iron ore production from underground activities, which provides step-by-step implementation of that process, and also gives the possibility to plan the activities of the enterprise.